ئاستی بەكارهێنانی ئامڕازەكانی میدیای نوێ لای مامۆستایانی باخچە لەشاری سلێمانیدا (توێژینەوەی هەڵێنجراو) - بۆكانی, صابر بكر مصطفی; حمەامین, أكرم فریدون; كریم, شاهۆ خوارحم (Sulaimani Journal for Humanities, 2023)
The aim of this study is to know the level of the use of new media of in teaching by kindergarten teachers in Sulaimani. And knowing the difference is statistically significant in the use of new media by kindergarten teachers according to certain variables such as: (sex, degree and age). In addition to determining the new media used by kindergarten teachers during teaching. To achieve these goals; the researcher depended the descriptive survey approach that is commensurate with the nature and objectives of the study. The research community includes all kindergarten teachers (governmental and non-governmental) in the Sulaimani City, and their number is (1187) teachers, which are distributed over education in eastern and western Sulaimani. The researcher selected 179 male and female teachers from his study community using the stratified random distribution method. In order to collect data and information, observation tools and the new media use scale were used, which were prepared by benefiting from previous research and composed of (85) items. To achieve the results, the researcher used several appropriate statistical tools through the statistical package for social sciences (SPSS version 26). Finally, the study concluded that the level of using new media in the teaching among kindergarten teachers in Sulaimani was at a high level. And it appeared that there are no statistically significant differences in the use of new media according to sex variable (male, female). But, there is a statistically significant difference in the use of new media tools according to degree variable and was in the interest of a bachelor's degree. Moreover, Data Show and multimedia were the two new media tools that were most used in teaching, and Viber and Facebook were the two social networking tools that were most used by kindergarten teachers.
Keywords: level; use; new media; kindergarten; kindergarten teacher